PENGARUH PENGGUNAAN MINYAK KELAPA SAWIT DAN RUMPUT LAUT DALAM RANSUM TERHADAP PERTUMBUHAN, SERTA KOMPOSISI KARKAS DAN NON KARKAS KELINCI - Mustafidah Udkhiyati (Buletin Peternakan, 2015)
The aim of this experiment was to study the effect of utilization of palm oil and seaweed in diet on abbit growth and carcass-non carcass composition. Twenty eight male Flemish Giant rabbits (the average age were 5 months) with average initial weight 1560±212 g were used in this research. All rabbits were randomly classified in four treatment in rations, they were R1 (control treatment = 0% palm oil+0% seaweed), R2 (5% palm oil+0% seaweed), R3 (0% palm oil+5% seaweed), R4 (2.5% palm oil+2.5% seaweed). Each treatment consists of seven replications. Individual cages (size 40x30x30 cm3) were used. The animals were reared during 40 days. All collected data were analyzed by One Way nova. The results showed that feed intake (gBK/rabbit/day) of all treatment groups were not significantly different. Meanwhile, the feed intake (gBK/BW) of R4 significantly lower (P<0.05) than others, they were R1 = 55.80±5.36 g, R2 = 55.20±8.04 g, R3 = 50.17±4.26 g, R4 = 46.25±2.21 g. Average daily gain of all treatment groups were not significantly different. Feed conversion ratio of all treatment groups were also not significantly different, they were R1 = 9.20±3.35, R2 = 6.40±1.67, R3 = 7.17±2.23 and R4 = 8.75±4.03. It is concluded that the utilization of palm oil and seaweed did not affect the feed consumption, average daily gain, feed conversion ratio and carcass-non carcass composition.(Key word: Average daily gain, Carcass, Feed conversion ratio, Feed intake, Palm oil, Seaweed)